Re-focusing School Curriculum: Shaping Educational Vision Around the New Capital City of Indonesia - Abdul Hakim; Susilo Susilo; Atin Nuryadin; Yuni Utami Asih; Sudarman Sudarman; Khusnul Khotimah; Nurul Fitriyah Sulaeman (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Human resource development is a key focus in the development of the Indonesian capital city. Elementary and secondary schools in Sepaku Regency, Penajam Paser Utara Regency, are the closest buffer zone to the New Capital City. Therefore, the quality of these schools is crucial in facilitating the development of the younger generation around the New Capital City. Adjustments to curriculum documents serve as guidelines for school administration, ensuring the quality of educational services provided. Therefore, training and mentoring in school curriculum development are crucial and have become the aim of this program. The method of this mentoring program was implemented through five phases from 2024 to 2025, with 12 elementary schools and two junior high schools in Sepaku District participating. The mentoring result demonstrated that each school was able to create comprehensive and aligned curriculum documents with a focus on in-depth learning. Challenges encountered during the training process included changes in the number of school representatives present at the training and mentoring activities. In early 2025, there was a shift in the curriculum guidelines toward in-depth learning. The finalization process for mentoring, incorporating key elements of in-depth learning into the curriculum documents, has been completed. It can be concluded that mentoring could support schools to re-focus their curriculum.